Development of low cost, lossy and low dielectric constant OPEFB-HDPE composite material for microwave application - Balami, Sunday Dauda (2017)
Oil palm empty fruit bunch fibre and high density polyethylene (OPEFB-HDPE) composites have been used in a variety of applications. However, it’s potentials as a lossy low dielectric substrate for microwaves applications has not been realized. To date, the application of biomaterials as fillers in composites for microwave applications have not been examined. Research on lossy low dielectric constant materials reported are limited to polymer and metal oxides composite which are much expensive, hence the need to study materials from organic source which are less expensive, biodegradable and abundantly available. This thesis presents the development of a lossy, low dielectric constant substrate based on OPEFB-HDPE composites for various microwave applications such as LTCC based patch antenna. This antenna require low dielectric constant and high loss factor factor (ε′ between 2.5 and 10.0, ε′′ ranges from 0.1 to 0.4). (ε′ between 2.5 and 10.0, ε′′ ranges from 0.1 to 0.4). OPEFB exhibit excellent mechanical properties when compared to other natural fibers. The OPEFB fibers are biodegradable, cheap and non-toxic compared to various other industrial materials. The higher the percentage of filler the more the absorption which is good for electromagnetic shielding as well various as microwave absorber application. The conventional solid-state method based on melt blend technique was used to prepared the composites. Five OPEFB-HDPE composites with different filler percentage were prepared. The complex permittivity of the composites were measured using open ended coaxial probe (OEC). The rectangular waveguide (RWG) was used to evaluate the scattering parameters and absorption. Finally, the resonance frequency was determined from the measured S-parameters of the microstrip patch antenna. The crystalline structure of the composites was analyzed using X-ray diffraction (XRD) machine. The dielectric properties, and the transmission and reflection coefficients were measured using PNA (N5227) Network Analyzer from 8 GHz to 12 GHz at room temperature. The theoretical calculation of the transmission and reflection coefficients and visualization of electric field distribution of the sample placed in the waveguide was computed using Finite Element Method (FEM) accomplished using COMSOL software. The permittivity of the composites was found to depend on the mixing ratio between OPEFB and HDPE. The dielectric constants of composites were found to be between 2.5 and 3.2 and the loss factor from 0.15 to 0.38 in the X-band frequency. Both Ɛ’ and Ɛ” of the composites can be predicted from the regression equations by inserting values of the fractional composition of the fillers. Both ε′and ε′′ of the OPEFB-HDPE composite increased with increasing percentages of OPEFB fillers. These, in turn, will lead to higher values of the magnitude reflection coefficient |S11| and lower transmission coefficient |S21| by the impedance matching theory. Comparison of the measured and calculated scattering parameters was also investigated. Furthermore, the results obtained from the scattering parameters were used to determine the effect of OPEFB on absorption properties of the composite samples. The electric field distribution through the waveguide was visualized using FEM simulation. Finally, the effect of the different percentage of OPEFB filler on resonance frequency was investigated by fabricating the composites into microstrip patch antenna at frequency range 1 GHz to 4 GHz. The resonance frequency was found to be in the range between 1.98 GHz to 2.16 GHz. It increases with the decrease in the filler content. The return loss was in the range -11.93 dB to -4.43 dB.